Etiological Categorization and Metabolic Disorders Associated with Recumbency in Dairy Cows in the Cauvery Delta Region of Tamil Nadu - Thamizharasi, A.; Veeraselvam, M.; Premalatha, N.; Kumar, S. Senthil; Saravanan, M.; Karthika, K.; Yogeshpriya, S.; Swamy, K. K. Ponnu; Tamileniyan, E. (International Journal of Bio-resource and Stress Management, 2026)
The present investigation was conducted from March, 2023 to November, 2023 at the Veterinary Clinical Complex (VCC), Veterinary College and Research Institute, Orathanadu, situated in the Cauvery delta zone of Tamil Nadu, India. Recumbent cow syndrome continues to be a major clinical and economic problem in dairy herds, especially during the transition period when metabolic demands are markedly increased. The study aimed to identify the etiological factors associated with recumbency and to evaluate the pattern of metabolic disorders contributing to downer cow syndrome in the Cauvery delta region of Tamil Nadu. A total of 156 recumbent dairy cows presented to the Teaching Veterinary Clinical Complex, Orathanadu, were included in the study. Detailed clinical examinations were performed, followed by serum biochemical analysis of calcium, phosphorus, magnesium, potassium, glucose, β-hydroxybutyrate and non-esterified fatty acids. Etiological classification revealed that metabolic disorders were the leading cause of recumbency, accounting for 59.6% of cases, followed by musculoskeletal, gastrointestinal, reproductive, infectious, and toxic conditions. Among the metabolic abnormalities, hypocalcaemia (40.1%) and concurrent hypocalcaemia with hypophosphatemia (25.8%) were most frequently observed, whereas hypophosphatemia, hypokalaemia, and hypomagnesemia constituted the remaining cases. Metabolic recumbency was significantly higher in post-parturient cows highlighting the increased susceptibility during the transition period. The findings emphasize the need for early metabolic profiling, balanced nutrition, and strategic mineral supplementation to reduce recumbency and improve dairy herd health in the region.